One-plasmid double-expression system for preparation of MS2 virus-like particles packaging SARS-CoV-2 RNA - Qi, Lili; Zhang, Zheng; Wang, Mengting; Ke, Zhijian; Mao, Haiguang; Deng, Gang; Wang, Jinbo (Frontiers in Cellular and Infection Microbiology, 2023)
COVID-19 is a disease caused by a virus named SARS-CoV-2. SARS-CoV-2 is a single-stranded positive-sense RNA virus. Reverse transcription quantitative PCR (RT–qPCR) assays are the gold standard molecular test for detection of RNA viruses. The aim of this study was to construct an RNA-positive control based on MS2 phage-like particles (MS2 VLPs) to detect SARS-CoV-2 RNA. pCDFDuet-1 was used as a one-plasmid double-expression system to construct MS2 VLPs containing ssRNA of SARS-CoV-2. The sequence encoding one copy of maturase, His-tag and coat protein dimer was cloned and inserted into MCS1 of the plasmid; the fragment encoding protein N and ORF1ab from SARS-CoV-2 was cloned and inserted into MCS2. The prepared plasmid was transformed into Escherichia coli strain BL2 (DE3), and expression of the construct was induced by 1 mM isopropyl-L-thio-D-galactopyranoside (IPTG) at 30°C for 12 hours. MS2 VLPs were purified and collected with Ni-NTA affinity chromatography columns. The size and shape of the MS2 VLPs were verified by transmission electron microscopy, and the stability of MS2 VLP packaged RNA was evaluated by treatment with RNase A. Effects of storage temperature and buffer on MS2 VLP stability were also investigated. The results showed that SARS-CoV-2 MS2 VLPs could be successfully produced by this one-plasmid double-expression system. MS2 VLPs showed high stability and may be used as a positive control in molecular diagnosis of COVID-19.